2021
DOI: 10.5771/0342-300x-2021-4-306
|View full text |Cite
|
Sign up to set email alerts
|

Tarifbindung und betriebliche Interessenvertretung: Ergebnisse aus dem IAB-Betriebspanel 2020

Abstract: Mit diesem Beitrag wird die jährliche Berichterstattung zur Tarifbindung und betrieblichen Interessenvertretung mit Daten für 2020 fortgesetzt. Zunächst wird die Tarifbindung der Betriebe nach Branche und Betriebsgröße dargestellt. Dabei wird auf die nach wie vor vorherrschenden Unterschiede zwischen West- und Ostdeutschland abgestellt. Insgesamt jedoch hat die Flächentarifbindung seit 1996 in beiden Landesteilen eine deutlich rückläufige Tendenz. Auch für die betriebliche Ebene der Mitbestimmung ist in der la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…In 1995, 72 percent of western German employees were covered by collectively agreed standards for wages, hours, and working conditions (multi‐employer agreement), however this share declined to 45 per cent by 2020 (and in eastern Germany from 56 percent in 1996 to 32 percent in 2020). (Ellguth & Kohaut, 2021 , p. 307). Similarly, the share of the western German workforce represented by a works council declined from 51 percent (1993) to 41 percent (2020) and in eastern Germany from 45 percent (1996) to 36 percent (2020) (Ellguth & Kohaut, 2021 , p. 314).…”
Section: Covid ‐19: a Stress Test For Declining Ir...mentioning
confidence: 99%
“…In 1995, 72 percent of western German employees were covered by collectively agreed standards for wages, hours, and working conditions (multi‐employer agreement), however this share declined to 45 per cent by 2020 (and in eastern Germany from 56 percent in 1996 to 32 percent in 2020). (Ellguth & Kohaut, 2021 , p. 307). Similarly, the share of the western German workforce represented by a works council declined from 51 percent (1993) to 41 percent (2020) and in eastern Germany from 45 percent (1996) to 36 percent (2020) (Ellguth & Kohaut, 2021 , p. 314).…”
Section: Covid ‐19: a Stress Test For Declining Ir...mentioning
confidence: 99%
“…Coverage of employees by industry-level collective agreements fell from some 70 per cent in the 1990s to below 50 per cent by 2020, with only just under 40 per cent of employees represented by a works council -a drop of some 10 percentage points in recent years. Less than 30 percent of employees work in workplaces that were covered by both a collective agreement and works council representation, the core of the dual system of German industrial relations (Ellguth and Kohaut, 2021). This has been exacerbated by a sharp decline in trade union density, with only about 16 percent of employees now union members compared to more than 30% in the 1980s and early 1990s.…”
Section: German Trade Unions and Work Councils -Trends And Developmentsmentioning
confidence: 99%
“…Currently, about 40% of the private sector and most public sector employees work in establishments that are covered by sectoral collective bargaining agreements. About 8% of employees are paid according to collective agreements negotiated at the firm level (Ellguth and Kohaut, 2021). The resulting bargaining coverage substantially exceeds union density of about 16% (OECD and AIAS, 2021).…”
Section: Institutional Settingmentioning
confidence: 99%
“…Collective bargaining and works councils often co-exist. However, there is a substantial fraction of firms in which only one of the two pillars of industrial relations can be observed (Ellguth and Kohaut, 2021).…”
Section: Institutional Settingmentioning
confidence: 99%
See 1 more Smart Citation